Preservative effects of sumac hydro-alcoholic extract and chitosan coating enriched along with Zataria multiflora Boiss essential oil on the quality of beef during storage - Mojaddar Langroodi, Ali (Vet Res Forum, 2018)
Beef is susceptible to rapid spoilage due to its high amount of protein (18.00%) and moisture (72.00%). Food industries have recently found methods to extend beef shelf-life. The influence of beef dipping in hydro-alcoholic extract of sumac (SE) and chitosan (CH) coating incorporated with Zataria multiflora essential oil (ZEO) on microbial, chemical and sensory quality of beef was evaluated during refrigerated storage. Total viable counts (TVC), lactic acid bacteria, Pseudomonas spp., Enterobacteriaceae and yeasts-molds, total volatile nitrogen (TVN), thiobarbituric acid reactive substance values (TBARS) and peroxide value (PV) were founded to be significantly lower in all treatment groups compare to control groups during storage time. The highest level of antimicrobial effects induced by chitosan, SE 4.00% and ZEO. We found that in TVC (3.69 log CFU g(-1) reduction compared with control group (sterile distilled water), Enterobacteriaceae (3.61 log CFU g(-1) reduction) and lactic acid bacteria (2.67 log CFU g(-1) reduction), respectively. Sumac gave a pleasant effect on sensory attributes and chitosan coating enriched with ZEO significantly improved sensory scores except for flavor factor. The results revealed the bio preservative properties of chitosan, hydro-alcoholic extract of sumac and Z. multiflora Boiss essential oil during refrigeration in normal packaging of beef.